Teknologi Kecerdasan Buatan Untuk Mengembangkan Desain Motif Batik Kontemporer - Rianto Rianto; Enny Itje Sela; Nur Wening (Universitas Teknologi Yogyakarta, 2024)
Artificial intelligence technology in producing contemporary batik motif designs is an innovative phase in the creative industry. The development of technology, Natural Language Processing, allows text to be translated into images, providing an excellent opportunity to accelerate the design process while enriching creative ideas. This community service program aims to train batik artisans in adopting information technology, especially artificial intelligence, to create new, attractive motif designs. The training includes using an AI-based platform and design transfer techniques to fabric media. The result of this activity is a contemporary batik motif that targets millennials with their distinctive style. This technology provides two main advantages: 1) time efficiency in design creation and 2) broad creative inspiration through automatic exploration of motif data. Both of these advantages show that the application of artificial intelligence in batik design supports innovation and competitiveness in the modern market.